MAPPING THE CONCEPT OF A GOOD SCHOOL WITH TEACHERS’ CHARACTERISTICS IN THE CONTEXT OF A GOOD SCHOOL CONCEPT - KRIAUČIŪNIENĖ, Roma; TARGAMADZĖ, VILIJA (Journal of Education Culture and Society, 2019)
Aim. The concept of Good School was formed in 2015, however, the implementation of it has been rather slow. Therefore, the research aim of this article is to identify the educational experts’ viewpoints on the concept. The following questions have been raised to specify the aim: if the concept of the school of general education, presented as Good School, is adequately understood, what features should a teacher have in order to implement the concept of Good School? Methods. To answer the research questions a qualitative research by using structured interviews was carried out, i.e. experts’ written surveys were analyzed. The study revealed three positions that are discussed in this article: the concept of Good School, the mission and teachers’ features, which are interpreted in the context of the concept of Good School, albeit in a particular way. Results. The analysis of the empirical research data revealed that insufficient emphasis is placed on the value aspect, modelling of community-based school activities and their reflection. The research findings also showed that there has been a considerable lack of attention paid to some of the teacher’s competences – there has been a lack of experts’ focus on the personalization of the educational content, its construction in the interaction with the elements of the pedagogical system, the reflection of pedagogical activities, and others. Conclusions. The concept of Good School is understood by the experts as a map, a conceptual idea, a guideline unfolding the schools’ specificity. The implementation of the concept of Good School should be based on the ideas of constructionism that open the pathways of common development, realization, and improvement of Good School.